A Storage-Driven CO2 EOR for a Net-Zero Emission Target. (November 2022) - Liu, Yueliang; Rui, Zhenhua
Graphical abstract: It presents a new generation of the CO2 EOR method—namely, storage-driven CO2 EOR—whose purpose is to realize net-zero or even negative CO2 emissions by sequestrating CO2 in oil reservoirs while maximizing oil recovery. Within the framework of such a method, CO2 enhanced oil recovery is harmonious and synergistic, but sometime contradictory, with carbon geological storage in oil reservoir geological body. New advanced technologies are necessary to be developed to weaken the antagonism but improve the synergy, of which the relationship is very like the "Tai Chi". Storage-driven CO2 EOR method provides a feasible way to a paradigm shift in hydrocarbon recovery from massive-emission process to a net-zero-emission one, which significantly reduces CO2 emission but increases the economic benefit of CO2 EOR. Abstract: Stabilizing global climate change to within 1.5 °C requires a reduction in greenhouse gas emissions, with a primary focus on carbon dioxide (CO2 ) emissions. CO2 flooding in oilfields has recently been recognized as an important way to reduce CO2 emissions by storing CO2 in oil reservoirs. This work proposes an advanced CO2 enhanced oil recovery (EOR) method—namely, storage-driven CO2 EOR—whose main target is to realize net-zero or even negative CO2 emissions by sequestrating the maximum possible amount of CO2 in oil reservoirs while accomplishing the maximum possible oil recovery. Here, dimethyl ether (DME) is employed as an efficient agent in assisting conventional CO2 EOR for oil recovery while enhancing CO2 sequestration in reservoirs. The results show that DME improves the solubility of CO2 in in situ oil, which is beneficial for the solubility trapping of CO2 storage; furthermore, the presence of DME inhibits the "escape" of lighter hydrocarbons from crude oil due to the CO2 extraction effect, which is critical for sustainable oil recovery. Storage-driven CO2 EOR is superior to conventional CO2 EOR in improving sweeping efficiency, especially during the late oil production period. This work demonstrates that storage-driven CO2 EOR exhibits higher oil-in-place (OIP) recovery than conventional CO2 EOR. Moreover, the amount of sequestrated CO2 in storage-driven CO2 EOR exceeds the amount of emissions from burning the produced oil; that is, the sequestrated CO2 offsets not only current emissions but also past CO2 emissions. By altering developing scenarios, such as water alternating storage-driven CO2 EOR, more CO2 sequestration and higher oil recovery can be achieved. This work demonstrates the potential utilization of DME as an efficient additive to CO2 for enhancing oil recovery while improving CO2 storage in oil reservoirs.